First-in-human clinical trial of transplantation of iPSC-derived NS/PCs in subacute complete spinal cord injury: Study protocol - Sugai, Keiko; Sumida, Miho; Shofuda, Tomoko; Yamaguchi, Ryo; Tamura, Takashi; Kohzuki, Tsuneo; Abe, Takayuki; Shibata, Reo; Kamata, Yasuhiro; Ito, Shuhei; Okubo, Toshiki; Tsuji, Osahiko; et al. (Regenerative therapy, 2021)
Our group has conducted extensive basic and preclinical studies of the use of human induced pluripotent cell (iPSC)-derived neural stem/progenitor cell (hiPSC-NS/PC) grafts in models of spinal cord injury (SCI). Evidence from animal experiments suggests this approach is safe and effective. We are preparing to initiate a first-in-human clinical study of hiPSC-NS/PC transplantation in subacute SCI. NS/PCs were prepared at a Good Manufacturing Practice-grade cell processing facility at Osaka National Hospital using a clinical-grade integration-free hiPSC line established by the iPSC Stock Project organized by the Kyoto University Center for iPS Cell Research and Application. After performing all quality checks, the long-term safety and efficacy of cells were confirmed using immunodeficient mouse models. The forthcoming clinical study uses an open-label, single-arm design. The initial follow-up period is 1 year. The primary objective is to assess the safety of hiPSC-NS/PC transplantation in patients with subacute SCI. The secondary objective is to obtain preliminary evidence of its impact on neurological function and quality-of-life outcomes. Four patients with C3/4-Th10 level, complete subacute (within 24 days post-injury) SCI will be recruited. After obtaining consent, cryopreserved cells will be thawed and prepared following a multi-step process including treatment with a γ-secretase inhibitor to promote cell differentiation. A total of 2 × 106 cells will be transplanted into the injured spinal cord parenchyma 14–28 days post-injury. Patients will also receive transient immunosuppression. This study protocol has been reviewed and approved by the Certified Committee for Regenerative Medicine and the Japanese Ministry of Health, Labor and Welfare (University Hospital Medical Information Network Clinical Trials Registry [UMIN-CTR] number, UMIN000035074; Japan Registry of Clinical Trials [jRCT] number, jRCTa031190228). We plan to start recruiting a patient as soon as the COVID-19 epidemic subsides. The primary focus of this clinical study is safety, and the number of transplanted cells may be too low to confirm efficacy. After confirming safety, a dose-escalation study is planned. •A first-in-human clinical study for spinal cord injury using iPSC-derived cells is about to begin.•The primary objective is to assess the safety of human iPSC-derived neural stem/progenitor cells.•Further clinical trials are expected to be conducted to statistically assess efficacy.